Элементы структурной модели устройства аппроксимации для задач идентификации и контроля параметров объектов управления - Жиленков, А.А.; Чёрный, С.Г. (Проблемы машиностроения, 2013)
Представлены результаты разработки адаптивного фильтра сигналов систем управления полупроводниковых преобразователей и активных фильтро-компенсирующих устройств, работающих в составе электроэнергетической системы ограниченной мощности. Фильтр позволяет осуществлять избирательное подавление высших гармоник в силовой сети. Наведені результати розробки адаптивного фільтра сигналів систем керування напівпровідникових перетворювачів та активних фiльтро-компенсуючих приладiв, що працюють у складі електроенергетичної системи обмеженої потужності. Фільтр дозволяє здійснювати виборче заглушення вищих гармонік в силовій мережі. For ships with a DC propulsion engine powered from AC voltage , and includes such elements of the system as a synchronous generator (SG), controlled rectifier, and the load in the form of electric propulsion DC induction motor, as for any autonomous system of this configuration , actual problem is the negative influence of powerful disturbing to the supply network . Taking into account the autonomy of the system described , it is necessary to take into account that the distortion of forms of currents and voltages ship directly affect the network and on the control system themselves that generate them . Due to the lack of security requirements in the scheme of the ship's power plant of neutral wire makes the system pulse shaping control power switches more critical to the observed distortions in the network in the form of network voltage unbalance on its inability to control the input and the output phase voltages SG.